Suboccipital steroid injection alone as a preventive treatment for cluster headache - Gonen, Murat; Balgetir, Ferhat; Aytac, Emrah; Tasci, Irem; Demir, Caner Feyzi; Mungen, Bulent (Elsevier Sci Ltd, 2019)
Background: Suboccipital steroid injection can be used as a preventive treatment for episodic and chronic cluster headache (CH). In recent studies, prophylactic treatment has been used in addition to suboccipital steroid injection. In this study, we aimed to investigate the effectivity of the sole use of rapid- and long-acting steroid injections without prophylactic treatment in patients with episodic and chronic CH. Methods: The retrospective study included 51 patients with episodic and chronic CH that underwent greater occipital nerve (GON) blockade with a single dose of rapid- and long-acting steroid injection without additional prophylactic treatment. The frequency, severity, and duration of attacks after GON blockade as well as the side effects and long-term outcomes were reviewed. Results: In 28 (54.9%) patients, no attack occurred after GON blockade and cluster bouts were aborted. Mean duration of attacks was 86.67 +/- 37.45 min before the treatment. However, in the 23 patients that had at least one attack after GON blockade, the mean duration of attacks was 31.73 +/- 36.10 min between post-treatment days 0-3, 29.35 +/- 40.49 min between post-treatment days 4-10, 28.48 +/- 42.17 min between post-treatment days 11-28, and 35.65 +/- 46.55 min after the post-treatment day 28 (p < 0.001). Moreover, 10 (37.04%) out of 27 patients with episodic CH who periodically had one or two cluster bouts in a year had no CH attack at the time of the expected subsequent cluster bout. Conclusion: GON blockade is a practical, reliable, and cost-effective treatment option for patients with episodic and chronic CH. Moreover, GON blockade is highly effective in reducing headache attacks and even aborting cluster bouts in CH patients without requiring additional prophylactic treatment. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Cluster headache; Greater occipital nerve blockade; Corticosteroid; Treatment